Child Temperament and Internalizing Symptoms: The Mediating Role of Resilience and Coping Flexibility - Shakibarad, Atefeh; Mosayebipour Dalivnd, Somayeh; Bahrami, Maryam (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to examine whether resilience and coping flexibility mediate the relationship between child temperament and internalizing symptoms among school-aged children.Methods and Materials: This study adopted a correlational design and was conducted on a sample of school-aged children recruited from public elementary and lower secondary schools in Tehran. Participants were selected using multistage cluster sampling, and data were collected through standardized parent-report questionnaires assessing child temperament, resilience, coping flexibility, and internalizing symptoms. After screening the data for missing values and normality assumptions, structural equation modeling was employed to test the hypothesized mediation model. Model fit was evaluated using multiple goodness-of-fit indices, and indirect effects were examined through bootstrapping procedures to determine the significance of mediational pathways.Findings: Structural equation modeling revealed a significant direct effect of child temperament on internalizing symptoms. Child temperament also showed significant negative effects on both resilience and coping flexibility. Resilience and coping flexibility, in turn, were significant negative predictors of internalizing symptoms. Indirect effect analyses indicated that resilience significantly mediated the relationship between temperament and internalizing symptoms, and coping flexibility also emerged as a significant mediator. The total indirect effect was significant, demonstrating that resilience and coping flexibility jointly accounted for a substantial portion of the association between child temperament and internalizing symptoms, while the direct path remained significant, indicating partial mediation.Conclusion: The findings suggest that child temperament influences internalizing symptoms not only directly but also indirectly through its impact on resilience and coping flexibility.